A quantitative metric for knee osteoarthritis: reference values of joint space loss - Ratzlaff, C.; Ashbeck, E. L.; Guermazi, A.; Roemer, Frank; Duryea, J.; Kwoh, C. K. (Osteoarthritis and Cartilage, 2018)
OBJECTIVES: Knee osteoarthritis (OA) onset and progression has been defined with transitions in Kellgren-Lawrence (KL) grade or Osteoarthritis Research Society International (OARSI) Joint Space Narrowing (JSN) grade. We quantitatively describe one-year transitions in KL grade and JSN, using fixed joint space width (fJSW), among knees with or at risk of OA. METHODS: Radiographic assessments from the Osteoarthritis Initiative (OAI) were used to identify transitions in KLG and JSN grade between consecutive annual visits. The fJSW was measured in the medial and lateral compartments. The distribution of change in fJSW for KLG and JSN transitions were described, and mean change in fJSW was estimated using mixed models. RESULTS: KL grade and JSN scores were available for about 20,000 annual transitions from 6047 knees contributed by 3389 participants. Knees that remained stable in KL or OARSI-JSN over 1 year had mean medial fJSW loss between -0.06 and -0.19 mm/year. Transition from KL grade 0 to 1, 0 to 2, and KL 1 to 2 were similar with respect to mean medial fJSW loss (0.18-0.28 mm). Greatest annual changes in medial fJSW corresponded to KL 0 to 3 (1.62 mm), KL 2 to 4 (1.23 mm) and JSN 0 to 2 (1.85 mm). CONCLUSIONS: Anchoring quantitatively measured loss of joint space width to transitions in KL grade and JSN provides reference values based on traditional definitions of knee OA onset and progression.
EVALuna2:36238